2015
DOI: 10.1155/2015/340616
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Ferroelectric Switchable Polarization and Leakage Current Behavior in (Ba0.50Sr0.50)(Ti0.80Sn0.20)O3 Thin Films Prepared Using Chemical Solution Deposition

Abstract: Nanoscale switchable ferroelectric (Ba0.50Sr0.50)(Ti0.80Sn0.20)O3-BSTS polycrystalline thin films with a perovskite structure were prepared on Pt/TiOx/SiO2/Si substrate by chemical solution deposition. X-ray diffraction (XRD) spectra indicate that a cubic perovskite crystalline structure and Raman spectra revealed that a tetragonal perovskite crystalline structure is present in the thin films. Sr2+and Sn4+cosubstituted film exhibited the lowest leakage current density. Piezoresponse Force Microscopy (PFM) tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Due to their unique combination of properties such as spontaneous and switchable polarization, piezoelectricity, and pyroelectricity, ferroelectricity, electrocaloric effect, photovoltaic effect and photocatalytic properties etc, perovskite‐based ferroelectric have been extensively studied for multifunctional applications including nonvolatile random access memories (NVRAMs), dynamic random access memories (DRAMs), high‐frequency (GHz) bypass capacitors, infrared detectors, as well as tunable devices in microwave electronics. In particular, ferroelectric materials are very much suitable for energy storage capacitors, multilayer ceramic capacitors (MLCCs), actuators, lead‐free piezoelectric transducers, and charge storage devices are particularly popular in power electronics, pulsed power applications, high‐power microwave systems etc 1‐5 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to their unique combination of properties such as spontaneous and switchable polarization, piezoelectricity, and pyroelectricity, ferroelectricity, electrocaloric effect, photovoltaic effect and photocatalytic properties etc, perovskite‐based ferroelectric have been extensively studied for multifunctional applications including nonvolatile random access memories (NVRAMs), dynamic random access memories (DRAMs), high‐frequency (GHz) bypass capacitors, infrared detectors, as well as tunable devices in microwave electronics. In particular, ferroelectric materials are very much suitable for energy storage capacitors, multilayer ceramic capacitors (MLCCs), actuators, lead‐free piezoelectric transducers, and charge storage devices are particularly popular in power electronics, pulsed power applications, high‐power microwave systems etc 1‐5 …”
Section: Introductionmentioning
confidence: 99%
“…Suitable site engineering, that is doping or substitution either at or both A and B sites of ABO 3 ‐type perovskites, plays an important role in controlling both chemical and physical properties of the materials. Usually doping or substitution of isovalent (like Sr 2+ , Ca 2+ , Pb 2+ , Mg 2+ for Ba 2+ and Zr 4+ , Sn 4+ , Mn 4+ for Ti 4+ ) or alio‐valent (like Ta 5+ , Sb 5+ , Nb 5+ , Mn 3+ , Mo 3+ , W 3+ , Fe 3+ for Ti 4+ and Sm 3+ , La 3+ , Pr 3+ , Gd 3+ for Ba 2+ ) in BaTiO 3 lattice can be done for improved properties 1‐5 . Here, in all cases, the cation with extra positive charges present in the dopant ions is compensated by excess electrons, which are assumed to be present in the Ti 3d‐ conduction band.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the influence of doping type on the formation of ferroelectric perovskite materials showed that iron doping induces the disappearance of ferroelectricity in (Pb,Sr)(Ti,Fe)O 3 thin films [8]. Puli et al [9] observed a strong domain switching response at nanoscale level by using PFM in (Ba 0.50 Sr 0.50 )(Ti 0.80 Sn 0.20 )O 3 thin films a. Furthermore, Huang et al [10] reported PFM images in which domain boundaries are in agreement with grain boundaries in Bi 3.15 Nd 0.85 Ti 3 O 12 ferroelectric thin films, suggesting that grain boundaries entirely confine the shape of domain boundaries.…”
Section: Introductionmentioning
confidence: 99%